Translation, cultural adaptation, and validation of the AOFAS lesser metatarsophalangeal-interphalangeal scale into Brazilian Portuguese - Araújo, Thaisa Assad; Rodrigues de Miranda , Bruno; Calvelli Coelho, Henrique; Marson Sanches, André; Campelo Lima Souza, Felipe; Diego Pupa de Freitas , Álvaro; Correa Paiva Fonseca Fonseca, Fabio; Ryuko Cândido Nishikawa , Danilo; Reis da Nóbrega, Tomás; dos Santos Barroco , Rui (Journal of the Foot & Ankle, 2025)
Objective: Translate, culturally adapt, and evaluate the reproducibility of the American Orthopaedic Foot and Ankle Society (AOFAS) lesser metatarsophalangeal-interphalangeal scale into Brazilian Portuguese. Methods: The AOFAS and SF-36 questionnaires were applied to 50 patients with lesser toes deformity. The methodology followed the criteria defined by Reichenheim & Moraes for translation and cultural adaptation of questionnaires. Result: The intraclass correlation coefficient (ICC) across the domains was 0.96, and Cronbach’s alpha was 0.80, both indicating excellent reliability. The scores of the first and second evaluations were 70.72 and 72.36, respectively, with high interobserver agreement and overlapping confidence intervals. Spearman’s correlation analysis also yielded a correlation coefficient of 96%, indicating strong agreement among the applications of the test. Conclusion: According to the established criteria, the translation and cultural adaptation of the questionnaire were conducted effectively, with very high interobserver agreement, and can be safely reproduced in Brazilian Portuguese. Level of evidence IV; Case series